Highly active antiretroviral therapy reduces mortality and morbidity in patients with AIDS in Sungai Buloh Hospital - Mat Shah, R.; Bulgiba, A.; Lee, C.K.C.; Haniff, J.; Mohamad Ali, M. (2012)
Background Highly active antiretroviral therapy (HAART) was introduced in Malaysia in 1997, but its effectiveness has never been evaluated. Methods This 12-year retrospective cohort study is the first attempt at evaluating the effectiveness of HAART in Malaysia. Records from Infectious Diseases Clinic, Hospital Sungai Buloh, from 1997 to 2008, were matched with the National Registration Department Death Records 1997-2008 and Selangor State HIV/AIDS/Death Surveillance database 1997-2008. Results The median survival time was 134 (95 confidence interval: 97.93-170.07) months. Those on HAART lived significantly longer. The HAART group had a lower all-cause mortality rate (almost 30 times fewer than those not on HAART,) and AIDS-defining events (at least 3 times less than those not on HAART). The mortality and morbidity of our patients were significantly lower with than without HAART. HAART should therefore be made accessible to all AIDS patients.